An Exploratory Study of Issues in Training Facilitators for Online Training in Advance Care Planning: Mixed Methods Research - Yuko Goto; Hisayuki Miura (MDPI AG, 2024)
Advance care planning (ACP) has attracted increasing research attention in recent years. In Japan, extensive training has been conducted to improve communication through workshops, such as role-playing. In training, including trainee-centered work, the facilitator who assists trainee learning plays an important role. However, only a few studies have focused on the training of facilitators. Therefore, we exploratorily analyzed by the mixed method the differences in the approaches of experienced and inexperienced facilitators during workshops and conducted a study that could contribute to facilitator training in the future. We recorded the comments and attitudes of 12 facilitators who participated in ACP training conducted in 2022. Based on analysis of the obtained data, a distinct difference was confirmed in the progression of trainee-based learning, encouragement to deepen learning among trainees, and trainees' responses to questions. Thus, this study indicated the importance of having the opportunity for fellow facilitators to learn through facilitation with experienced facilitators and involvement in issue awareness.